Design of web‐tapered steel members through a stiffness reduction method. (13th September 2017) - Kucukler, Merih; Gardner, Leroy; Macorini, Lorenzo
ABSTRACT: Stiffness reduction provides a practical means for the instability assessment of structural steel members. In this paper, a stiffness reduction approach for the design of web‐tapered steel members fabricated through the welding of individual plates is presented. Stiffness reduction functions for welded members, which fully take into account the adverse influence of plasticity and imperfections on the strength and stability, are described. The proposed approach is implemented by (i) dividing the tapered member into prismatic segments along its length, (ii) reducing the flexural stiffness of each segment through the developed stiffness reduction functions considering the withstood forces and the cross‐section properties of each segment, (iii) performing Geometrically Nonlinear Analysis using beam elements and (iv) making cross‐section strength checks. The accuracy of the proposed approach is assessed against the results of nonlinear shell finite element modelling for a large number of tapered members, with various slenderness values, tapering ratios (i.e. the ratios between the cross‐section depths of deep and shallow ends) and loading conditions. It is observed that the proposed stiffness reduction method provides a very accurate and efficient way to design web‐tapered steel members.